Intention Activation Strategy to promote health and prevention against diseases in police officers (Research, Society and Development, 2022)
Purpose: Reflecting about the Intention Activation Strategy for the practice of physical activity in police officers. Methods: sustained reflection in the light of scientific evidence which shows to the importance of the Attention Activation Strategy to encourage the practice of physical activity. Results: This paper studies the need of special care based on disease prevention. It is believed that the Attention Activation Strategy applied through the use of mobile telemessaging can be an effective strategy for health promotion, behavior improvement taking into consideration the level of physical activity and prevention of health problems in police officers. Final considerations: despite the lack of protocols for this public, the importance of this theoretical framework is perceived in order to motivate and guide the encouragement of physical activity as a strategy to prevent health problems in police officers.